Protocol for a randomised controlled trial for Reducing Arthritis Fatigue by clinical Teams (RAFT) using cognitive–behavioural approaches. Issue 8 (6th August 2015) - Hewlett, S; Ambler, N; Almeida, C; Blair, P S; Choy, E; Dures, E; Hammond, A; Hollingworth, W; Kirwan, J; Plummer, Z; Rooke, C; Thorn, J; et al.
Abstract : Introduction: Rheumatoid arthritis (RA) fatigue is distressing, leading to unmanageable physical and cognitive exhaustion impacting on health, leisure and work. Group cognitive–behavioural (CB) therapy delivered by a clinical psychologist demonstrated large improvements in fatigue impact. However, few rheumatology teams include a clinical psychologist, therefore, this study aims to examine whether conventional rheumatology teams can reproduce similar results, potentially widening intervention availability. Methods and analysis: This is a multicentre, randomised, controlled trial of a group CB intervention for RA fatigue self-management, delivered by local rheumatology clinical teams. 7 centres will each recruit 4 consecutive cohorts of 10–16 patients with RA (fatigue severity ≥6/10). After consenting, patients will have baseline assessments, then usual care (fatigue self-management booklet, discussed for 5–6 min), then be randomised into control (no action) or intervention arms. The intervention, Reducing Arthritis Fatigue by clinical Teams (RAFT) will be cofacilitated by two local rheumatology clinicians (eg, nurse/occupational therapist), who will have had brief training in CB approaches, a RAFT manual and materials, and delivered an observed practice course. Groups of 5–8 patients will attend 6×2 h sessions (weeks 1–6) and a 1 hr consolidation session (week 14) addressing different self-management topics and behaviours. The primary outcome is fatigue impact (26 weeks); secondary outcomes are fatigue severity, coping and multidimensional impact, quality of life, clinical and mood status (to week 104). Statistical and health economic analyses will follow a predetermined plan to establish whether the intervention is clinically and cost-effective. Effects of teaching CB skills to clinicians will be evaluated qualitatively. Ethics and dissemination: Approval was given by an NHS Research Ethics Committee, and participants will provide written informed consent. The copyrighted RAFT package will be freely available. Findings will be submitted to the National Institute for Health and Care Excellence, Clinical Commissioning Groups and all UK rheumatology departments. Trial registration number: ISRCTN: 52709998; Protocol v3 09.02.2015.